2012
DOI: 10.1007/s00421-012-2321-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between decreased swimming velocity and muscle activity during 200-m front crawl

Abstract: The aims of this study were (1) to evaluate changes in muscle activity associated with physiological fatigue and decreased swimming velocity (SV) during 200 m of front crawl swimming, and (2) to examine the relationship between the decreased SV and changes in kinematic or electromyogram parameters. Twenty swimmers participated in a 4 × 50-m swim test. The surface EMG of 11 muscles (7 in the upper limbs and 4 in the lower limbs) was measured and the mean amplitude value (MAV) for one stroke cycle was obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 18 publications
2
51
0
3
Order By: Relevance
“…(24,25) We have not found studies in the literature that sought to observe the EMG frequency spectral characteristics (fatigue index) of inspiratory muscles in throwing athletes. Nevertheless, Stirn, (12) Ikuda (13) and Lomax (14) corroborated in part with our findings, since they saw the presence of fatigue through the EMG, the pectoralis major muscle, which carries double mechanical function during sporting gesture of swimmers, generated by high mechanical requirement for the gesture and simultaneous activation in the process of inspiration at high intensities of exercise. However, they did not assess the symmetry of the tested muscles, making it difficult to infer information of asymmetric responses in inspiratory fatigue of athletes evaluated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(24,25) We have not found studies in the literature that sought to observe the EMG frequency spectral characteristics (fatigue index) of inspiratory muscles in throwing athletes. Nevertheless, Stirn, (12) Ikuda (13) and Lomax (14) corroborated in part with our findings, since they saw the presence of fatigue through the EMG, the pectoralis major muscle, which carries double mechanical function during sporting gesture of swimmers, generated by high mechanical requirement for the gesture and simultaneous activation in the process of inspiration at high intensities of exercise. However, they did not assess the symmetry of the tested muscles, making it difficult to infer information of asymmetric responses in inspiratory fatigue of athletes evaluated.…”
Section: Discussionsupporting
confidence: 88%
“…(10) Recent studies have investigated, through the EMG, the fatigue index of upper limb muscles performing dual mechanical function during the sporting gesture, as the pectoralis major muscle, in which muscle fatigue was observed with reduction of EMG median frequency after maximum activities sports. (11)(12)(13)(14) However, we found no studies that verify the fatigue of inspiratory muscles compared to the shoulder lifting movement in throwing athletes. One study found the sternocleidomastoid (SCM) muscle behavior against the lifting of the arms, for ergonomic analysis, showing the occurrence of co-activation of this muscle against the motion.…”
Section: Introductionmentioning
confidence: 88%
“…The studies on rehabilitation utilised sEMG electrodes to measure the TB activity of patients of stroke [21][22][23][24], spinal cord injury [25][26][27][28], cerebral palsy [29], gait disorder [8,30], fatigue injury [20,31], and joint stability injury [17] during their trials. In contrast, the sports-based studies applied sEMG electrodes to measure the TB activity of athletes during the following sports activities: tennis [32][33][34], karate [35,36], pole vaulting [37], swimming [38,39], and dart throwing [40]. In addition, the sEMG activities of the TB were compared between healthy subjects and patients [21,22,24,28].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…During the following movement: reaching out from a starting position, picking up a cylinder, and returning it to the starting position Seventeen of the studies used bipolar or triode silver/silver chloride (Ag/AgCl) sEMG electrodes, one study [39] utilised bipolar gold sEMG electrodes, and one study [29] applied polycarbonate sEMG electrodes for the recording of the EMG activity on the TB. In addition, one study used a linear array of four silver bar sEMG electrodes [32].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation